2021
DOI: 10.3390/molecules26051387
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Gallocatechin Gallate on Glutamate-Induced Oxidative Stress in Hippocampal HT22 Cells

Abstract: Oxidative stress leads to protein degeneration or mitochondrial dysfunction, causing neuronal cell death. Glutamate is a neurotransmitter that nerve cells use to send signals. However, the excess accumulation of glutamate can cause excitotoxicity in the central nervous system. In this study, we deciphered the molecular mechanism of catechin-mediated neuroprotective effect on glutamate-induced oxidative stress in mouse hippocampal neuronal HT22 cells. Cellular antioxidant activity was determined using the 1,1-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The oxidative stress induced by glutamate will trigger the changes in the structure and function of the neurons and cause the death of neurons [ 14 , 24 ]. Earlier studies showed that plant extracts and compounds with strong antioxidant activity protected glutamate-induced neuronal death [ 4 , 25 ]. In the current study, we used mouse-derived hippocampal HT22 cells to study the neuroprotective effect of NGR1 against glutamate-induced cell apoptosis and to explore the neuroprotective mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative stress induced by glutamate will trigger the changes in the structure and function of the neurons and cause the death of neurons [ 14 , 24 ]. Earlier studies showed that plant extracts and compounds with strong antioxidant activity protected glutamate-induced neuronal death [ 4 , 25 ]. In the current study, we used mouse-derived hippocampal HT22 cells to study the neuroprotective effect of NGR1 against glutamate-induced cell apoptosis and to explore the neuroprotective mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction has an integral role in the development of oxidative stress and leads to increased oxidative stress, while the ultrastructure of mitochondria is destroyed, which further exacerbates mitochondrial dysfunction [ 28 ]. Plant extracts with antioxidant activity can inhibit glutamate-induced mitochondrial dysfunction and increase in Ca 2+ concentration in HT22 cells [ 25 ]. In this study, we found that NGR1 has an effect on mitochondrial dysfunction and Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…(-)-Epigallocatechin-3-gallate (EGCG) is a polyphenol that is abundantly found in tea ( Butt et al, 2015 ). EGCG shows a variety of functions in many diseases, such as antiarteriosclerosis ( Liu S. et al, 2017 ), antioxidant ( Park et al, 2021 ), antibacterial ( Noor Mohammadi et al, 2019 ), anti-inflammatory ( Ma et al, 2021 ), and anti-tumor activities ( Farabegoli and Pinheiro, 2022 ). The flow cytometry results of the study ( Tian et al, 2020 ) conducted by Tian et al showed that EGCG could inhibit the apoptosis and cell cycle arrest induced by H 2 O 2 .…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%
“…UDLS was found to be an effective antioxidant that may be helpful in recovery from brain injury. It could be developed as an antiapoptotic supplement, promoting cell survival in the brain [ 69 , 70 ].…”
Section: Antioxidant Potential Of Udmentioning
confidence: 99%